2007
DOI: 10.1111/j.1467-8276.2007.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Ex Ante Approaches to Obtain Credible Signals for Value in Contingent Markets: Evidence from the Field

Abstract: While contingent valuation remains the only option available for measurement of total economic value of nonmarketed goods, the method has been criticized due to its hypothetical nature. We analyze field experimental data to evaluate two ex ante approaches to attenuating hypothetical bias, directly comparing value statements across four distinct referenda: hypothetical, "cheap talk", "consequential", and real. Our empirical evidence suggests two major findings: hypothetical responses are significantly different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…The stylized fact from the broad literature is that there exists a positive and economically meaningful "hypothetical bias", whereby people tend to overstate their values in hypothetical settings (List and Gallett, 2001;Little and Berrens, 2004;Murphy, Stevens and Weatherhead, 2005). On the other hand, when the focus is put on consequentiality of the survey, the evidence supports the view that one-shot dichotomous choice stated preference methods possess criterion validity (Carson et al, 2004;Johnston, 2006;Landry and List, 2007;Vossler and Evans, 2009;Vossler and Kerkvliet, 2003). Furthermore some studies have identified behavior in consequential (but non-incentive compatible elicitation settings) that is consistent with mechanism design theory predictions (Bateman et al, 2008;Carson et al, 2004;Polomé, 2003).…”
Section: Introductionsupporting
confidence: 55%
“…The stylized fact from the broad literature is that there exists a positive and economically meaningful "hypothetical bias", whereby people tend to overstate their values in hypothetical settings (List and Gallett, 2001;Little and Berrens, 2004;Murphy, Stevens and Weatherhead, 2005). On the other hand, when the focus is put on consequentiality of the survey, the evidence supports the view that one-shot dichotomous choice stated preference methods possess criterion validity (Carson et al, 2004;Johnston, 2006;Landry and List, 2007;Vossler and Evans, 2009;Vossler and Kerkvliet, 2003). Furthermore some studies have identified behavior in consequential (but non-incentive compatible elicitation settings) that is consistent with mechanism design theory predictions (Bateman et al, 2008;Carson et al, 2004;Polomé, 2003).…”
Section: Introductionsupporting
confidence: 55%
“…This results are in line with the National Oceanic and Atmospheric Administration's blue ribbon panel (NOOA's BRP) recommendation, which suggested that hypothetical bids be deflected using a "divide by 2" [23,24] approach when using the contingent valuation method (another technique affiliated to the stated preference family). In addition to that, researchers have found [22,25,26] that HB tends to be smaller when: (1) goods assessed are private, as opposed to public; (2) people are asked to state their willingness to pay (WTP) instead of their willingness to accept (WTA); (3) experiments are realistic (i.e., payment vehicles are familiar and people rely on the feasibility to provide the attributes of the assessed goods) (In addition to that, researchers have designed ex ante and ex post techniques to reduce HB. The first includes "cheap talks" [27] and reminders of individuals' budgets, while the second includes special statistical techniques, such as stochastic frontier regressions [28]); and (4) individuals are carefully selected so as to ensure convenient experience and appropriate demographics.…”
Section: Methodology and Case Studymentioning
confidence: 99%
“…The cheap talk script has been suggested as a device to reduce or even eliminate hypothetical bias Taylor 1999, Landry andList 2007). The effect of cheap talk is, however, ambiguous in the literature.…”
Section: Related Literaturementioning
confidence: 99%